Responding to the COVID-19 Outbreak in Singapore: Staff Protection and Staff Temperature and Sickness Surveillance Systems. (21st April 2020) - Htun, Htet Lin; Lim, Dwee Wee; Kyaw, Win Mar; Loh, Wan-Ning Janis; Lee, Lay Tin; Ang, Brenda; Chow, Angela
Abstract: Background: Coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by a novel coronavirus (SARS-CoV-2) and first reported in Wuhan, China, in December 2019. Since the severe acute respiratory syndrome (SARS) outbreak in 2003, Tan Tock Seng Hospital (TTSH) in Singapore has routinely fit-tested staff for high-filtration N95 respirators and established Web-based staff surveillance systems. The routine systems were enhanced in response to Singapore's first imported COVID-19 case on 23 January 2020. Methods: We conducted a cross-sectional study from 23 January to 23 February 2020 among healthcare workers to evaluate the effectiveness of the staff protection and surveillance strategy in TTSH, a 1600-bed multidisciplinary acute-care hospital colocated with the 330-bed National Centre for Infectious Diseases (NCID). As of 23 February 2020, TTSH/NCID has managed 76% of confirmed COVID-19 cases in Singapore. The hospital adopted a multipronged approach to protect and monitor staff with potential COVID-19 exposures: (1) risk-based personal protective equipment, (2) staff fever and sickness surveillance, and (3) enhanced medical surveillance of unwell staff. Results: A total of 10 583 staff were placed on hospitalwide fever and sickness surveillance, with 1524 frontline staff working in COVID-19 areas under close surveillance. Among frontline staff, a median of 8 staff illness episodes was seen per day; almost 10% (n = 29) resulted in hospitalization. None of the staff was found to be infected with COVID-19. Conclusions: A robust staff protection and health surveillance system that is routinely implemented during non–outbreak periods and enhanced during the COVID-19 outbreak is effective in protecting frontline staff from the infection. Abstract : A robust staff protection and health surveillance system that is routinely implemented can be quickly enhanced and customized for specific emerging infectious diseases, and rapidly deployed during outbreaks, to protect staff from nosocomial infections.